A questionnaire study on the knowledge, attitudes, and practices of fluid replacement and urination among Chinese elite athletes - Song, G.; Yan, Y.; Zhao, H.; Chen, J.; Deng, Y. Zhu, W.; Sun, L.; Ma, G. (PLOS ONE, 2022)
Objective To evaluate the knowledge, attitudes and practices (KAP) of Chinese elite athletes about fluid replacement and urination. Methods A cross-section study was carried out among Chinese national and national youth teams from March to April 2020, using a pretested questionnaire. The 42-questions questionnaire was designed to assess the KAP regarding fluid replacement and urination. The questionnaire included knowledge of fluid replacement (KFR), attitudes of fluid replacement (AFR), knowledge of urination (KU), and attitudes of urination (AU), which were awarded 20 scoring points. Descriptive statistics, independent samples t-tests, one-way ANOVA, Pearson`s correlation analysis, Multiple linear stepwise regression and Chi-square test were performed. Results A total of 779 valid questionnaires were collected and the effective rate is 98.4%. We finally conducted an assessment of 646 questionnaires of elite athletes. The mean score for KFR, AFR, KU, and AU was 2.8±1.3, 2.3±0.6, 3.0±1.5, and 2.1±0.8, respectively, with higher scores indicating positive hydration knowledge and attitudes. KFR and AFR scores of winter sports athletes were higher than those of summer sports athletes(P<0.05). Athletes who had lower athletic grades and training years had a worse KFR(P<0.05). Only 31.0% athletes knew that rehydration should be carried out before, during, and after training, which was scarcer among women, lower-athletic grades athletes, or athletes with lower training years (P<0.05). Male athletes had a worse KU but a better AU than female athletes(P<0.05). And athletes who were international-class athletic grades had the highest KU scores(P<0.05). The athletic grades and sport events were the main factors influencing the total scores of knowledge and attitudes (P<0.05, 95% CI -0.789--0.168,95% CI 0.025-1.040). Most of athletes tend to get hydration knowledge from internet. In practices, thirst is the main reason for rehydration (77.9%). The percentages of athletes with normal urine color (42.0%), frequency (75.0%,) and volume (20.0%) were low. Conclusions These findings indicate that Chinese elite athletes did not have sufficient KAP on fluid replacement and urination, more marked in the individuals who were summer sport events, the lower athletic grades and in lower training years. It is recommended that education should be provided in the early stages of professional training for athletes.